The SAGE handbook of economic geography - Leyshon, Andrew (SAGE, 2011)
This companion illustrates the significance of thinking the 'economy' and the 'economic' geographically. It identifies significant stages in the discipline's development, and focuses on the key themes and ideas that inform present thinking in economic geography.